Estimation of the Ice-Induced Fatigue Damage to a Semi-Submersible Platform under Level Ice Conditions - Yoon-Chul Shin; Jeong-Hwan Kim; Yooil Kim (Applied Sciences, 2023)
This study presents a fatigue analysis procedure for inclined structures operated in level ice fields. Three methods for calculating the local ice load causing fatigue damage, namely the direct method, simplified method, and semi-analytical method, were introduced and compared. The direct method uses finite element analysis to simulate the continuous breaking of ice, while the simplified method and the semi-analytical method estimate the probability distribution of local ice loads based on theoretical equations and empirical data. The fatigue damage ratio at the target location was calculated by applying the ice load calculated by each method to a deformable finite element model of the structure. The results obtained from each method indicate that they provide a reasonable estimation of the local ice load causing fatigue damage in level ice fields. The direct method offers high accuracy but requires significant computational time, while the simplified method and semi-analytical method offer a faster analysis time and are more suitable for long-term time domain analysis. The semi-analytical method requires empirical data to supplement theoretical formulas due to the complex natural phenomena involving various environmental conditions that must be modeled. The findings of this study provide valuable insights into the prediction of fatigue damage in ice-going ships due to long-term ice impacts. The methods proposed in this study can aid in the design of Arctic ships exposed to various conditions and provide a more cost-effective and time-efficient approach to evaluating fatigue damage compared to field measurement. Future research in this field could investigate the application of these methods to other types of structures and further refine the methodology to improve accuracy and reduce computational costs.